2018
DOI: 10.1080/07420528.2018.1454938
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in repeated sprint performance cannot be offset when rectal and muscle temperatures are at optimal levels (38.5°C)

Abstract: The present study investigated whether increasing morning rectal temperatures (T) to evening levels, or increasing morning and evening T to an "optimal" level (38.5°C), resulting in increased muscle temperatures (T), would offset diurnal variation in repeated sprint (RS) performance in a causal manner. Twelve trained males underwent five sessions [age (mean ± SD) 21.0 ± 2.3 years, maximal oxygen consumption (V̇Omax) 60.0 ± 4.4 mL.kg min, height 1.79 ± 0.06 m, body mass 78.2 ± 11.8 kg]. These included control m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 59 publications
4
28
0
Order By: Relevance
“…In the current study left and right isometric grip strength followed the previously reported daily fluctuation with highest values in the evening than the morning and a variation of 4.6 % and 6.5 % of the 24-h mean, -similar to 6 % values reported by Reilly et al (2007). Furthermore, a diurnal variation in resting Trec values of 0.53°C was found, similar to values previously reported (Edwards et al 2013;Pullinger et al 2014Pullinger et al , 2018aPullinger et al , 2018bRobertson et al 2018). Our findings agree with current literature regarding time-of-day variation in Trec and muscle force output (Edwards et al 2013).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the current study left and right isometric grip strength followed the previously reported daily fluctuation with highest values in the evening than the morning and a variation of 4.6 % and 6.5 % of the 24-h mean, -similar to 6 % values reported by Reilly et al (2007). Furthermore, a diurnal variation in resting Trec values of 0.53°C was found, similar to values previously reported (Edwards et al 2013;Pullinger et al 2014Pullinger et al , 2018aPullinger et al , 2018bRobertson et al 2018). Our findings agree with current literature regarding time-of-day variation in Trec and muscle force output (Edwards et al 2013).…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, this is only the second study to demonstrate diurnal variation in bench press and back squat, but the first to assess the effect of an active warm-up on multi-joint exercises. Relatively few studies have looked at precise modelling of pre-exercise temperature (by removing individuals from the active warming stimulus when the required Trec was reached) through an active warm-up (Edwards et al 2013;Pullinger et al 2018a). It has previously been established that the use of an active warm-up of standard duration (Sim et al 2009;Taylor et al 2013;Yaicharoen et al 2012), results in producing large variations in core and/or Tm within individuals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations